The Spleen-to-Liver Ratios in Hepatic Diseases - Vorne, M.; Jurvelin, J.; Vähätalo, S.; Himanka, E. (Nuklearmedizin - NuclearMedicine, 1984)
We compared light pen (LPEN) and Region of Interest (ROI) computer methods in determining spleen-toliver (S/L) ratios both in anterior and posterior images in various liver diseases. The S/L ratio was independent of age or type of colloid used (equal particle size provided). Results with corresponding LPEN and ROI programs did not differ significantly from each other. The sensitivity and specificity were tested and the anterior view yielded somewhat better results than the posterior view but the best results were obtained when both projections were used. The sensitivity for all liver diseases was 60% and the corresponding specificity 93%. In hepatocellular diseases the sensitivity was 80-100%, but the S/L ratio had only 37% sensitivity for hepatic metastases. Hepatomegaly in the anterior view was found in 67% of fatty liver cases, in 25% of cirrhosis cases, in 20% of hepatitis and in 25% of metastatic livers. Splenomegaly was noted in 39-54% of patients with hepatocellular diseases but only in 4-10% of metastatic diseases.